The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1542/peds.2017-1975
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Clinician Suspicion of Lyme Disease in the Emergency Department

Abstract: Because clinician suspicion had only minimal accuracy for the diagnosis of Lyme disease, laboratory confirmation is required to avoid both under- and overdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In a previous prospective study of >1000 patients presenting to the ED for evaluation of Lyme disease, clinician suspicion had only minimal accuracy for the diagnosis of Lyme disease. 23 This work reveals PEDIATRICS Volume 141, number 5, May 2018 5 28,29 and several patients had a history of previous Lyme disease. In fact, 1 patient with septic arthritis and a positive Lyme disease 2-tiered serology result was assumed to have previous immunity.…”
Section: Discussionmentioning
confidence: 80%
“…In a previous prospective study of >1000 patients presenting to the ED for evaluation of Lyme disease, clinician suspicion had only minimal accuracy for the diagnosis of Lyme disease. 23 This work reveals PEDIATRICS Volume 141, number 5, May 2018 5 28,29 and several patients had a history of previous Lyme disease. In fact, 1 patient with septic arthritis and a positive Lyme disease 2-tiered serology result was assumed to have previous immunity.…”
Section: Discussionmentioning
confidence: 80%
“…Some physicians, faced with deciding whether or not to treat a patient for LD solely on the basis of clinical signs, but without serologic confirmation, opt for treatment with antibiotics. 23 Antibiotics are sometimes offered to patients who seek treatment for chronic fatigue, intermittent or persistent pain, and/or neurocognitive dysfunction, among other symptoms; this is controversial (see below). Some patients believe they may be suffering from “chronic LD”, a clinical syndrome for which there is no precise definition, diagnostic test, or definitive immediate response to appropriate antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence is high enough that all children presenting with facial nerve palsy in endemic areas should have Lyme serology performed. This is particularly important as it has been demonstrated that clinical features alone perform poorly at being able to determine the likelihood of Lyme aetiology (14), and outcomes following treatment of Lyme disease are excellent, recently confirmed by large adult population studies in Europe of Lyme neuroborreliosis (15).…”
Section: Discussionmentioning
confidence: 99%